2016
DOI: 10.1371/journal.pntd.0004208
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Helminth Infection and Environment in the Development of Allergy: A Prospective Study of Newly-Arrived Ethiopian Immigrants in Israel

Abstract: Helminth infection may be protective against allergy and account for the low prevalence of allergy in developing countries. We studied prospectively the prevalence of allergy in Ethiopian immigrants with heavy helminth infection on arrival in Israel, and again after a year of adjustment to an urban industrialized setting, to explore the roles of helminth infection, changed environment and background immunity on the manifestations of allergy. 126 newly arrived Ethiopian immigrants were studied at baseline and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
1
29
3
Order By: Relevance
“…These findings are comparable to observations from Europe showing that children born on a farm (usually in rural areas) have a lower risk of asthma in later life, even when they subsequently moved to urban areas (27), and that children who migrated to Europe after age five had a lower prevalence of asthma, similar to their country of origin, than children who were either born in Europe or migrated before the age of five (28,29). However, there are also studies that show increased risk of wheezing and allergy among children following migration (30,31). Unlike studies from Europe and North America which have reported a lower risk of asthma for children born or raised on farms (32,33), our study found no association between asthma risk and exposure to farm animals either during pregnancy or in early life.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to observations from Europe showing that children born on a farm (usually in rural areas) have a lower risk of asthma in later life, even when they subsequently moved to urban areas (27), and that children who migrated to Europe after age five had a lower prevalence of asthma, similar to their country of origin, than children who were either born in Europe or migrated before the age of five (28,29). However, there are also studies that show increased risk of wheezing and allergy among children following migration (30,31). Unlike studies from Europe and North America which have reported a lower risk of asthma for children born or raised on farms (32,33), our study found no association between asthma risk and exposure to farm animals either during pregnancy or in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stein and colleagues examined the burden of helminth infections among 126 immigrants from Ethiopia newly arrived in Israel and related these to allergy outcomes [ 20 •]. The most prevalent helminth infection detected was hookworm (73.1%) followed by S. mansoni infection (47.2%) [ 20 •].…”
Section: Helminth Infections and Clinical Presentations Of Allergic Dmentioning
confidence: 99%
“…One year post-anthelmintic treatment, an increase in allergy symptoms was observed in treated individuals. Stein et al 2016 [ 20 •] …”
Section: Introductionmentioning
confidence: 99%
“…Geohelminth can cause nutritional disorders and anemia, especially in children with less nutritional intake [2]. Behind these negative effects, worms turned out to provide protective effects on some diseases such as allergies, which have been proven by many researchers [3,4,5]. This turned out to be related to the ability of worms to modulate the immune response of the host [6,7].…”
Section: Introductionmentioning
confidence: 99%